Awareness About Mood Changes in Dental Students - Sheefaa. M. I, Dr. Subasree S (South Eastern European Journal of Public Health, 2025)
Introduction: Increased level of psychological disturbances such as depression, anxiety, and stress among dental students, affect the way these students take care of patients. Aim: To analyse the awareness about mood swings in dental students. Materials and Methods: A self structured questionnaire was created to analyse the awareness about mood swing in dental students, this study is performed to make the students cope up with their mood changes. Results: Based on the study we could analyse the students who are susceptible to theses higher level of psychological problems like stress, anxiety, and depression, we can provide them supportive programs and make them cope up with these conditions..